Study of Distribution, Potential and Habitat of Harpullia arborea in the Frame of Establishment of In-Situ Gene Bank at Kerinci Seblat National Park - Sambas Basuni; Haidir . (Department of Forest Resources Conservation and Ecotourism - IPB University, 1997)
The study was conducted at Muara Emat and Tamiai Resort of Karinci Seblat Nationel Park. The study was d o r i g 4 for d i r h m n e t of